2015
DOI: 10.1002/2014gl062874
|View full text |Cite
|
Sign up to set email alerts
|

Van Allen Probes show that the inner radiation zone contains no MeV electrons: ECT/MagEIS data

Abstract: We present Van Allen Probe observations of electrons in the inner radiation zone. The measurements were made by the Energetic Particle, Composition, and Thermal Plasma/Magnetic Electron Ion Spectrometer (MagEIS) sensors that were designed to measure electrons with the ability to remove unwanted signals from penetrating protons, providing clean measurements. No electrons >900 keV were observed with equatorial fluxes above background (i.e., >0.1 el/(cm 2 s sr keV)) in the inner zone. The observed fluxes are comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
134
1
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 35 publications
20
134
1
1
Order By: Relevance
“…REPT represents a state‐of‐art instrument for accurately measuring the energetic particles in the magnetosphere—both REPT instruments on the twin Van Allen Probes show identical features throughout their entire orbits, including the outer belt, slot region, and the inner belt. This, supported by the high‐quality measurements of the MagEIS instruments that show no measurable >800 keV electrons in the inner belt [ Fennell et al , ], leaves little doubt that the upper limits of MeV electrons bounded by REPT measurements should be the standard for future model improvement, at least for periods like the last few years when no extreme solar wind conditions were observed.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…REPT represents a state‐of‐art instrument for accurately measuring the energetic particles in the magnetosphere—both REPT instruments on the twin Van Allen Probes show identical features throughout their entire orbits, including the outer belt, slot region, and the inner belt. This, supported by the high‐quality measurements of the MagEIS instruments that show no measurable >800 keV electrons in the inner belt [ Fennell et al , ], leaves little doubt that the upper limits of MeV electrons bounded by REPT measurements should be the standard for future model improvement, at least for periods like the last few years when no extreme solar wind conditions were observed.…”
Section: Discussionmentioning
confidence: 94%
“…Fennell et al [] have shown that the energy spectrum of relativistic electrons in the inner belt is very steep and the flux of ≥ 800 keV electrons are already at the background noise level of the MagEIS, while the flux of < 400 keV electrons is even higher than the AE9 mean value as shown in Figure .…”
Section: Discussionmentioning
confidence: 95%
“…For E > Q the spectra approximate a power law ∼ E −4 . Also shown for comparison are exponential energy spectra that approximate electron intensity measured at L = 1.5, from the DEMETER low‐altitude satellite during 2009 for E < 800 keV [ Selesnick , ] and from Van Allen Probes near the magnetic equatorial plane during 2014 for E < 900 keV [ Fennell et al , ]. As there are no reliable measurements of higher‐energy electrons, the measured spectra are extrapolated to higher energies assuming the same exponential shapes.…”
Section: Trapped Electron Intensitymentioning
confidence: 99%
“…Until recently it had been thought that the inner radiation belt electron intensity at any energy was much too high for a CRAND source [ Lyons and Thorne , ; Walt and Farley , ]. However, it is now apparent that electron measurements for E0.3em0.3em0.3em1 MeV were contaminated by the abundant high‐energy protons, and the actual high‐energy electron intensity is much lower than previously thought [ Li et al , ; Fennell et al , ], except following a rare injection of higher‐energy electrons [ Blake et al , ]. Therefore, it is now of interest to reexamine the CRAND source of electrons, with particular attention to the high‐energy component that was not computed previously.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a good rule-of-thumb is that below about 700 keV, electron data in the inner belt is relatively safe to use. Latest results showed that there is an impenetrable barrier to ultrarelativistic electrons in the Van Allen radiation belts and that the inner radiation zone contains no MeV electrons by analyzing ECT-MagEIS data (Fennell et al 2015). Given the above facts, our study therefore focuses on hundreds of keV energetic electrons (∼350-450 keV) in the inner radiation belt with data from "Pixel" 3 and 4 of unit MED75-A,B (see Table 1 for details) from 7 September 2012 to 29 January 2015.…”
Section: Van Allen Probes Mission and Databasementioning
confidence: 99%